The evidence-based practice : methods, models, and tools for mental health professionals - Stout, Chris E.; Hayes, Randy A. (John Wiley & Sons, Inc., 2005)
"Evidence-Based Practice (EBP), a trend started in the medical community, is rapidly becoming of critical importance to the mental health profession as insurance companies begin to offer preferential pay to organizations using it. Featuring contributions from top researchers in the field, this groundbreaking book covers everything from what EBP is and its relevance to behavioural health to specific models for application and implementation, building best practice protocols, and evaluating bottom-line effectiveness in your organization"--Provided by publisher